Meretas Hubungan Mayoritas-Minoritas dalam Perspektif Nilai Bugis - Syarifuddin Latif (Al-Ulum, 2012)
The raise of conflicts due to the gap between the majority and the minority in the social stratum is getting more and more progressing recently. The conflicts, of course, are a serious problem tham must overcome because they can corrupt the harmony of life. To minimize the conflicts, both the majority and the minority must be harmonized by using some efforts. One effort that can be offered is local wisdom of the buginesss that is called paseng and pangadereng. Paseng consists of ada tongeng, sipakatau sipakalebbi, dan mappesona ri dewata seuwwae. Meanwhile pangadereng consists of adek, rapang, bicara, warik, dan sarak, local wisdom of the buginesss is expected to contribute effectifely in the effort to build a harmony relationship between the majority and the minority.